Az igazságosság a magyar büntetőjogi kódex-tervezetekben - László, Balázs (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
One of the important measures of the quality of the criminal procedure is the role of justice in the principles and specific rules of the procedure. However, from a historical perspective, justice in criminal proceedings can be of many kinds. We can talk, among other things, about the justice of the victim, the parties, the community, the judge or even the defendant. In a more recent comparison, we can examine the relationship between material justice and procedural justice. In this study, I examine the appearance of justice in the codification attempts – in the Penal Code bills – of the end of the 18th century and the first half of the 19th century. However, when analyzing this era, the traditional Hungarian law of the previous centuries cannot be ignored either. And as a result, we can see that during historical development and the codification, certain factors that promote justice increasingly come to the force, while certain old solutions that work against justice are pushed back. However the solutions of the era do not fully meet or contemporary expectations of justice.